2019
DOI: 10.1507/endocrj.ej18-0353
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of 20 Japanese patients with insulinoma treated with diazoxide

Abstract: Diazoxide is recognized as an effective medical treatment for insulinoma. However, due to its adverse effects, such as fluid retention, it is sometimes difficult to employ diazoxide at an effective dose in clinical practice. This study aimed to clarify the clinical factors, which may affect efficacy and safety of the diazoxide treatment. We retrospectively evaluated the medical records of 20 patients with insulinoma including 4 malignant cases. The patients were divided into two groups according to the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 18 publications
1
6
0
1
Order By: Relevance
“…Regarding side effects, diazoxide induces fluid retention and thrombocytopenia 2,4) , especially in females 4) , which is consistent with our findings. In contrast, somatostatin analogs can cause malabsorption, cholelithiasis, and hypoglycemia 2) , and inhibit the secretion of counterregulatory hormones, such as glucagon, paradoxically inducing hypoglycemia 2) .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Regarding side effects, diazoxide induces fluid retention and thrombocytopenia 2,4) , especially in females 4) , which is consistent with our findings. In contrast, somatostatin analogs can cause malabsorption, cholelithiasis, and hypoglycemia 2) , and inhibit the secretion of counterregulatory hormones, such as glucagon, paradoxically inducing hypoglycemia 2) .…”
Section: Discussionsupporting
confidence: 92%
“…Approximately three patients per million suffer from insulinoma annually 2 ) ; because Japan is an aging society, the number of elderly patients with insulinoma may increase in the future. This is problematic because, although most insulinomas are benign, curative surgery is the primary treatment 2 , 3 , 4 ) . In the elderly, surgery is not always possible because of aging, disease progression, and comorbidities 5 ) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…He was initially managed with diazoxide, a medication that suppresses insulin secretion by directly opening ATP-dependent potassium channels on the beta-cell membrane. Previous clinical reviews have reported adequate glycemic control using diazoxide in approximately 50% of patients [6]. Medical management is often necessary in the preoperative period or in the management of cases in which surgery is contraindicated.…”
Section: Discussionmentioning
confidence: 99%